Peningkatan Motivasi Kinerja Guru Bahasa Indonesia Melalui Supervisi Akademik Pada Sekolah Binaan Di SMPN 35 Kerinci Semester Genap Tahun Ajaran 2022/2023 - Gusmarni Yelmita (Departement of Mathematics Education, 2024)
This research aims to discuss and obtain information regarding Increasing Indonesian Language Teacher Performance Motivation through Academic Supervision at Assisted Schools at SMPN 35 Kerinci Even Semester for the 2022/2023 Academic Year. The type of research carried out is school action research (PTS). This research was conducted at one of the target schools at SMPN 35 Kerinci. This research was carried out in the even semester of the 2022/2023 academic year, starting in January 2023. The research subjects were 5 Indonesian language teachers at SMPN 35 Kerinci. The research procedure consists of two cycles with four research stages starting from planning, implementation, observation and reflection. Data collection techniques in this research are interviews, observation and discussion. The data were analyzed using percentages. The results of the research show that implementing academic supervision can increase the work motivation of Indonesian language teachers at one of the author's schools, namely SMPN 35 Kerinci, which is characterized by an increase in the percentage of work motivation starting from the pre-cycle of 68.67% in the sufficient category. and in cycle II it increased to 88% in the very good category.